A lightweight, corrosion-resistant and UV-resistant floating material
By using composite modified gangue in floating materials and introducing light-stabilized functionalized silicones, the existing floating materials are solved in the balance between lightweight and mechanical properties, and their resistance in seawater and ultraviolet light environments is significantly improved.
Patent Information
- Application Number
- CN202411055022.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-02
AI Technical Summary
Existing floating materials are difficult to balance between lightweight and mechanical properties, and they perform poorly under strong corrosion and strong ultraviolet light environments.
Compound modified gangue is used as filler, and photostable functionalized silicones are introduced through surface grafting reaction to form a corrosion-resistant and ultraviolet-resistant floating material.
The lightweight and mechanical properties of floating materials have been improved, while significantly improving their corrosion resistance and UV resistance.
Smart Images

Figure BDA0004976120460000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of floating material preparation, and in particular, relates to a lightweight, corrosion-resistant and UV-resistant floating material. Background Art
[0002] With the development of the marine economy, the application scope of floating materials on water is becoming wider and wider, such as floating bodies used in offshore photovoltaic systems, offshore wind power generation floating bodies, dock floating bodies, etc. These offshore floating bodies need to be lightweight in design to facilitate later offshore laying. The existing floating materials are generally made of polyethylene materials through foaming. During the preparation process of such floating materials, inorganic fillers need to be added to increase the strength of the floating body so that the floating body can be used as a load-bearing substrate at sea. However, the addition of inorganic fillers often causes an increase in the density of the floating body, which runs counter to the goal of lightweighting the floating body. Moreover, these offshore floating bodies need to cope with the strong corrosive environment of seawater, and at the same time, they also need to cope with the strong ultraviolet light environment at sea.
[0003] Based on the above problems, the present invention provides a floating material which is lightweight, has excellent mechanical properties, is corrosion-resistant, and is resistant to ultraviolet light. Summary of the invention
[0004] The purpose of the present invention is to provide a corrosion-resistant and UV-resistant floating material to solve the problem that the existing floating materials are difficult to combine lightweight and mechanical properties, and the corrosion resistance and UV resistance properties need to be improved.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A corrosion-resistant and ultraviolet-resistant floating material comprises the following raw materials in parts by weight: 80-92 parts of HDPE, 8-20 parts of composite modified coal gangue, 0.5-1.2 parts of foaming agent, and 0.5-1.2 parts of foam stabilizer.
[0007] Furthermore, the composite modified coal gangue is prepared by surface grafting reaction of lightweight modified coal gangue and light-stable functionalized siloxane.
[0008] Furthermore, the mass ratio of the lightweight modified coal gangue to the light-stable functionalized siloxane is 10:2-4.
[0009] Furthermore, the surface grafting reaction conditions are: reaction temperature is 55-65° C., and reaction time is 4-6 h.
[0010] Preferably, the surface grafting reaction of the lightweight modified coal gangue and the light-stable functionalized siloxane is as follows:
[0011] At 55-65°C, under stirring, spray the ethanol solution of photostable functionalized siloxane into the mixed suspension of lightweight modified coal gangue. After spraying is complete, continue to keep warm and stir for 4-6 hours, stop the reaction, age, take the precipitate, wash it alternately with water and ethanol, and dry it to obtain the composite modified coal gangue.
[0012] The mixed suspension of lightweight modified coal gangue is prepared by mixing lightweight modified coal gangue, water and ethanol in a mass ratio of 1-3:4-8:15-20.
[0013] In the above-mentioned surface grafting reaction, the highly active silanol bonds formed by the hydrolysis of the siloxane chains in the light-stable functionalized siloxane are coupled and grafted with the active sites in the lightweight modified coal gangue, so that the surface of the lightweight modified coal gangue is grafted with the light-stable functionalized siloxane, and at the same time, siloxane chains and light-stable functional bonds (the hindered amine structure is derived from 2,2,6,6-tetramethylpiperidine) are introduced into the surface of the lightweight modified coal gangue.
[0014] Furthermore, the lightweight modified coal gangue is obtained by enzymatically hydrolyzing and pore-forming reaction of coated porous coal gangue obtained by mixing starch, water and acid-modified coal gangue, spray-drying and granulating, and composite enzyme in sodium acetate and acetic acid buffer solution.
[0015] Furthermore, the added mass of the complex enzyme is 0.1-0.3% of the mass of the coated porous coal gangue.
[0016] Furthermore, the complex enzyme is prepared by mixing saccharifying enzyme and α-amylase in a mass ratio of 1-2:3-4.
[0017] Furthermore, the pH of the sodium acetate and acetate buffer solution is 4.5-5.
[0018] Furthermore, the reaction temperature of the enzymatic hydrolysis pore-forming reaction is 30-50° C., and the reaction time is 24-30 h.
[0019] Preferably, the lightweight modified coal gangue is prepared by the following steps:
[0020] Mixing the coated porous coal gangue and a buffer solution of sodium acetate and acetic acid to form a suspension;
[0021] Add complex enzyme to the obtained suspension, then heat to 30-50°C for enzymolysis for 24-30 hours, then add sodium hydroxide solution to the enzymolysis reaction system and stir to inactivate the enzyme, then wash with water, wash with ethanol, and dry to obtain lightweight modified coal gangue. This step realizes coated porous modification and achieves the purpose of lightweighting.
[0022] The porous structure in the lightweight modified coal gangue includes the porous structure of the acid-modified coal gangue itself and the porous starch layer formed by enzymatic hydrolysis of starch coated on its surface. It has both active sites of acid-modified porous coal gangue pores and active sites of starch enzymatic hydrolysis. It is a composite layer with multiple reactive active sites (to improve the grafting rate of light-stable functionalized siloxane in subsequent surface grafting reactions), inorganic layers and organic layers, and composite porous particles.
[0023] Furthermore, the mass ratio of the coated porous gangue, sodium acetate and acetic acid buffer solution is 20-25:100.
[0024] Furthermore, in the reaction for obtaining the coated porous coal gangue, the mass ratio of starch, water and acid-modified coal gangue is 0.08-0.2:6-8:1.
[0025] Furthermore, the acid-modified coal gangue is obtained by soaking the porous coal gangue in 2-2.5M hydrochloric acid for 8-12 hours, then washing, drying and grinding.
[0026] Furthermore, the particle size of the acid-modified coal gangue is 100-150 meshes.
[0027] Furthermore, the light-stable functional siloxane is prepared by a functional silane coupling agent prepared by a ring-opening grafting reaction of an epoxy silane coupling agent with 2,2,6,6-tetramethylpiperidinamine through amino and epoxy groups, and then undergoing a hyperbranched hydrolysis reaction.
[0028] Furthermore, in the ring-opening grafting reaction of the amino group and the epoxy group, the molar ratio of the epoxy silane coupling agent to 2,2,6,6-tetramethylpiperidine is 1-1.2:1.
[0029] Furthermore, in the ring-opening grafting reaction of the amino group and the epoxy group, the reaction conditions are: the reaction solvent is ethanol, the pH is 9.5-10, the reaction temperature is 50-65° C., and the reaction time is 6-12 h.
[0030] Furthermore, the hyperbranched hydrolysis reaction is: the mixed system of the functional silane coupling agent and water is hydrolyzed at a pH of 5-5.5 and a temperature of 50-55° C. for 5-8 hours.
[0031] Furthermore, the mass ratio of the functional silane coupling agent to water is 2:5-8.
[0032] Preferably, the reaction for obtaining the light-stable functionalized siloxane comprises:
[0033] After the epoxy silane coupling agent, ethanol and 2,2,6,6-tetramethylpiperidine are uniformly mixed, the pH of the reaction system is adjusted to 9.5-10 by sodium hydroxide solution under condensation reflux stirring, and the mixture is heated to 50-65° C., stirred and reacted for 6-12 hours, cooled and stopped the reaction, and the ethanol is recovered by rotary evaporation, redissolved with dichloromethane, washed with water, separated, and the organic phase is rotary evaporated and dried to obtain a functional silane coupling agent;
[0034] After the functional silane coupling agent and water are mixed, the pH of the reaction solution is adjusted to 5-5.5 by concentrated hydrochloric acid, and the temperature of the reaction solution is maintained at 50-55° C. The reaction is stirred for 5-8 hours, and then the water is dried by spin drying to obtain light-stable functional siloxane.
[0035] Furthermore, the foaming agent and the foam stabilizer are additives well known to those skilled in the art, and are not limited to specific types in the present invention.
[0036] Beneficial effects of the present invention:
[0037] The invention provides a lightweight, corrosion-resistant and UV-resistant floating material, which utilizes coal gangue as a filler to realize waste utilization. Secondly, in view of the problems of the accumulation of coal gangue and the weak reinforcing effect of the filler, the invention successively performs acid soaking and grinding modification, starch surface pore-forming lightweight modification and chemical resistance modification on the coal gangue. Among them, the acid modification solves its accumulation problem, while improving its modification activity and giving it a porous structure. The starch surface pore-forming lightweight modification introduces a starch layer into the solid particles to form an inorganic core layer and an organic layer. The double-layer structure improves the filler reinforcement effect of the coated porous coal gangue. At the same time, the lightweight pores are created again, which increases the complexity of the pores in the coated porous coal gangue, further gives the coated porous coal gangue lightweight characteristics, and improves the reaction activity of the coated porous coal gangue. The last step of chemical resistance modification is to graft a layer of light-stable functional siloxane on the coated porous coal gangue, giving the resulting composite modified coal gangue UV resistance (achieved by the hindered amine structure) and chemical resistance (achieved by the hyperbranched siloxane chain).
[0038] In summary, the present invention solves the problem that the introduction of existing fillers easily causes an increase in the density of floating materials through the introduction of composite modified coal gangue, while achieving the purpose of lightweighting the floating material and enhancing the mechanical properties. The floating material obtained by the present invention has excellent corrosion resistance and UV resistance. DETAILED DESCRIPTION
[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] Obtaining photostable functionalized siloxanes:
[0042] A1. After uniformly mixing 0.1 mol of epoxy silane coupling agent, 60 mL of ethanol and 0.1 mol of 2,2,6,6-tetramethylpiperidine, the pH of the reaction system was adjusted to 9.5-10 by sodium hydroxide solution under condensation reflux stirring, and heated to 50°C, stirred and reacted for 12 hours, cooled to stop the reaction, and the ethanol was recovered by rotary evaporation, redissolved with dichloromethane, washed with water, separated, and the organic phase was rotary evaporated and dried to obtain a functional silane coupling agent;
[0043] A2. After mixing the functional silane coupling agent and water in a mass ratio of 2:5, the pH of the reaction solution was adjusted to 5-5.5 by concentrated hydrochloric acid, and the temperature of the reaction solution was maintained at 50° C. The reaction was stirred for 8 hours, and then the water was dried and dried to obtain a light-stable functional siloxane.
[0044] Example 2
[0045] Obtaining photostable functionalized siloxanes:
[0046] A1. After uniformly mixing 0.12 mol of epoxy silane coupling agent, 60 mL of ethanol and 0.1 mol of 2,2,6,6-tetramethylpiperidine, the pH of the reaction system was adjusted to 9.5-10 by sodium hydroxide solution under condensation reflux stirring, and heated to 65°C, stirred and reacted for 6 hours, cooled to stop the reaction, and the ethanol was recovered by rotary evaporation, redissolved with dichloromethane, washed with water, separated, and the organic phase was rotary evaporated and dried to obtain a functional silane coupling agent;
[0047] A2. After mixing the functional silane coupling agent and water in a mass ratio of 2:8, the pH of the reaction solution was adjusted to 5-5.5 by concentrated hydrochloric acid, and the temperature of the reaction solution was maintained at 55° C. The reaction was stirred for 5 hours, and then the water was dried and dried to obtain a light-stable functional siloxane.
[0048] Example 3
[0049] Obtaining composite modified coal gangue:
[0050] B1. Soak the coal gangue in 2M hydrochloric acid for 12 hours, then wash, dry, grind, and pass through a 100-mesh sieve to obtain acid-modified coal gangue; then mix the acid-modified coal gangue, starch, and water in a mass ratio of 1:0.08:6, and then spray-dry and granulate to obtain coated porous coal gangue;
[0051] B2. The coated porous gangue obtained in step B1 and a buffer solution of sodium acetate and acetic acid (pH 4.5-5) are mixed in a mass ratio of 20:100 to form a suspension; a composite enzyme prepared by mixing saccharifying enzyme and α-amylase in a mass ratio of 1:3 is added to the obtained suspension, and then the mixture is heated to 30° C. for enzymolysis for 30 hours, and then a sodium hydroxide solution is added to the enzymolysis reaction system and stirred to inactivate the enzyme, and then the mixture is washed with water, washed with ethanol, and dried to obtain a lightweight modified gangue, wherein the added mass of the composite enzyme is 0.1% of the mass of the coated porous gangue.
[0052] Example 4
[0053] Obtaining composite modified coal gangue:
[0054] B1. Soak the coal gangue in 2.5M hydrochloric acid for 8 hours, then wash, dry, grind, and pass through a 150-mesh sieve to obtain acid-modified coal gangue; then mix the acid-modified coal gangue, starch, and water in a mass ratio of 1:0.2:8, and then spray-dry and granulate to obtain coated porous coal gangue;
[0055] B2. The coated porous gangue obtained in step B1 and a buffer solution of sodium acetate and acetic acid (pH 4.5-5) are mixed in a mass ratio of 25:100 to form a suspension; a composite enzyme prepared by mixing saccharifying enzyme and α-amylase in a mass ratio of 2:3 is added to the obtained suspension, and then the mixture is heated to 50° C. for enzymolysis for 24 hours, and then a sodium hydroxide solution is added to the enzymolysis reaction system and stirred to inactivate the enzyme, and then the mixture is washed with water, washed with ethanol, and dried to obtain a lightweight modified gangue, wherein the added mass of the composite enzyme is 0.3% of the mass of the coated porous gangue.
[0056] Example 5
[0057] Obtaining composite modified coal gangue:
[0058] Under stirring at 55° C., the ethanol solution of the photostable functionalized siloxane prepared in Example 1 was sprayed into the mixed suspension of the lightweight modified coal gangue obtained in Example 3 (the mixed suspension of the lightweight modified coal gangue was prepared by mixing the lightweight modified coal gangue obtained in Example 3, water, and ethanol in a mass ratio of 1:4:15). After the spraying was complete, the mixture was kept warm and stirred for 4 hours, the reaction was stopped, aged, the precipitate was taken, washed alternately with water and ethanol, and dried to obtain a composite modified coal gangue, wherein the mass ratio of the lightweight modified coal gangue to the photostable functionalized siloxane was 10:2.
[0059] Example 6
[0060] Obtaining composite modified coal gangue:
[0061] Under stirring at 65° C., the ethanol solution of the photostable functionalized siloxane prepared in Example 2 was sprayed into the mixed suspension of the lightweight modified coal gangue obtained in Example 4 (the mixed suspension of the lightweight modified coal gangue was prepared by mixing the lightweight modified coal gangue obtained in Example 4, water, and ethanol in a mass ratio of 3:8:20). After the spraying was complete, the mixture was kept warm and stirred for 6 hours, the reaction was stopped, aged, the precipitate was taken, washed alternately with water and ethanol, and dried to obtain a composite modified coal gangue, wherein the mass ratio of the lightweight modified coal gangue to the photostable functionalized siloxane was 10:4.
[0062] Comparative Example 1
[0063] Obtaining composite modified coal gangue:
[0064] Under stirring at 55° C., the ethanol solution of the photostable functionalized siloxane prepared in Example 1 was sprayed into the mixed suspension of the acid-modified coal gangue obtained in Example 3 (the mixed suspension of the lightweight modified coal gangue was prepared by mixing the acid-modified coal gangue obtained in Example 3, water, and ethanol in a mass ratio of 1:4:15). After the spraying was complete, the mixture was kept warm and stirred for 4 hours, the reaction was stopped, aged, the precipitate was taken, washed alternately with water and ethanol, and dried to obtain a composite modified coal gangue, wherein the mass ratio of the lightweight modified coal gangue to the photostable functionalized siloxane was 10:2.
[0065] Example 7
[0066] Preparation of floating materials:
[0067] C1. Prepare the following raw materials in parts by weight: 80 parts of HDPE, 20 parts of the composite modified coal gangue prepared in Example 5, 0.5 parts of a foaming agent, and 0.5 parts of a foam stabilizer; the foaming agent is foaming agent 141B, and the foam stabilizer is B8870;
[0068] C2. After drying and mixing the raw materials prepared in step C1, add them into a blow molding machine and perform blow molding (foaming ratio 1.2) to obtain a floating material (thickness 30 mm).
[0069] Example 8
[0070] Preparation of floating materials:
[0071] C1. Prepare the following raw materials in parts by weight: 87 parts of HDPE, 13 parts of the composite modified coal gangue prepared in Example 6, 1 part of a foaming agent, and 1 part of a foam stabilizer; the foaming agent is foaming agent 141B, and the foam stabilizer is B8870;
[0072] C2. After drying and mixing the raw materials prepared in step C1, add them into a blow molding machine and perform blow molding (foaming ratio 1.3) to obtain a floating material (thickness 30 mm).
[0073] Example 9
[0074] Preparation of floating materials:
[0075] C1. Prepare the following raw materials in parts by weight: 92 parts of HDPE, 8 parts of the composite modified coal gangue prepared in Example 5, 1.2 parts of a foaming agent, and 1.2 parts of a foam stabilizer; the foaming agent is foaming agent 141B, and the foam stabilizer is B8870;
[0076] C2. After drying and mixing the raw materials prepared in step C1, add them into a blow molding machine and perform blow molding (foaming ratio 1.5) to obtain a floating material (thickness 30 mm).
[0077] Comparative Example 2
[0078] Preparation of floating material: Compared with Example 7, an equal amount of the composite modified coal gangue is replaced with the composite modified coal gangue prepared in Comparative Example 1, and the rest is the same.
[0079] Comparative Example 3
[0080] Preparation of floating material: Compared with Example 7, an equal amount of the composite modified coal gangue is replaced with the acid-modified coal gangue prepared in step B1 of Example 3, and the rest is the same.
[0081] Comparative Example 4
[0082] Preparation of floating material: Compared with Example 7, an equal amount of the composite modified coal gangue was replaced with 100-mesh coal gangue, and the rest was the same.
[0083] Comparative Example 5
[0084] Preparation of floating material: Compared with Example 7, an equal amount of composite modified coal gangue is replaced by HDPE, and the rest is the same.
[0085] The physical properties of the floating materials obtained in Examples 7-9 and Comparative Examples 2-5 were tested, and the test results are shown in Table 1.
[0086] Table 1
[0087]
[0088] It can be seen from the data in Table 1 that the floating material obtained in Examples 7-9 of the present invention has excellent lightweight, compression strength, UV resistance and corrosion resistance.
[0089] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0090] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A lightweight, corrosion-resistant and UV-resistant floating material, characterized in that , including the following raw materials by weight: 80-92 parts of HDPE, 8-20 parts of composite modified coal gangue, 0.5-1.2 parts of foaming agent, and 0.5-1.2 parts of foam stabilizer; The composite modified coal gangue is prepared by surface grafting reaction of lightweight modified coal gangue and light-stable functionalized siloxane; The lightweight modified coal gangue is obtained by mixing starch, water and acid-modified coal gangue, spray-drying and granulating the coated porous coal gangue, and performing enzymatic hydrolysis and pore-forming reaction of composite enzyme in sodium acetate and acetic acid buffer solution; The light-stable functional siloxane is prepared by a functional silane coupling agent prepared by a ring-opening grafting reaction of an epoxy silane coupling agent with 2,2,6,6-tetramethylpiperidinamine through amino and epoxy groups, and then undergoing a hyperbranched hydrolysis reaction; The mass ratio of the lightweight modified coal gangue and the light-stable functionalized siloxane is 10:0.7-1.5, and the surface grafting reaction conditions are: the reaction temperature is 55-65° C., and the reaction time is 4-6 hours; The added mass of the composite enzyme is 0.1-0.3% of the mass of the coated porous gangue, the composite enzyme is prepared by mixing saccharifying enzyme and α-amylase in a mass ratio of 1-2:3-4, the pH of the sodium acetate and acetic acid buffer solution is 4.5-5, and the mass ratio of the coated porous gangue, sodium acetate and acetic acid buffer solution is 20-25:100; In the reaction for obtaining the coated porous coal gangue, the mass ratio of starch, water and acid-modified coal gangue is 0.08-0.2:6-8:1; In the ring-opening grafting reaction of the amino group and the epoxy group, the molar ratio of the epoxy silane coupling agent to 2,2,6,6-tetramethylpiperidine is 1-1.2:1; During the hyperbranched hydrolysis reaction of the functional silane coupling agent, the mass ratio of the functional silane coupling agent to water is 2:5-8.
2. A lightweight, corrosion-resistant and UV-resistant floating material according to claim 1, characterized in that: The reaction temperature of the enzymatic pore-forming reaction is 30-50° C., and the reaction time is 24-30 hours.
3. The lightweight, corrosion-resistant and UV-resistant floating material according to claim 1, characterized in that: The acid-modified coal gangue is obtained by soaking the porous coal gangue in 2-2.5M hydrochloric acid for 8-12 hours, then washing, drying and grinding.
4. The lightweight, corrosion-resistant and UV-resistant floating material according to claim 3, characterized in that: The particle size of the acid-modified coal gangue is 100-150 meshes.
5. The lightweight, corrosion-resistant and UV-resistant floating material according to claim 1, characterized in that: In the ring-opening grafting reaction of the amino group and the epoxy group, the reaction conditions are: the reaction solvent is ethanol, the pH is 9.5-10, the reaction temperature is 50-65° C., and the reaction time is 6-12 hours.
6. The lightweight, corrosion-resistant and UV-resistant floating material according to claim 1, characterized in that: The hyperbranched hydrolysis reaction is as follows: a mixed system of the functional silane coupling agent and water is hydrolyzed for 5-8 hours at a pH of 5-5.5 and a temperature of 50-55°C.
Citation Information
Patent Citations
Temperature-adjusted and modified recycled ascon composition for reusing 100% of waste ascon for road pavement, and method for manufacturing same
CN102448907A
Modified coal gangue-based fire prevention and extinguishing three-phase foam material as well as preparation method and application thereof
CN115120922A